THE IMPACT OF LONG-TERM USE OF SWEDISH SNUS ON THE RISK OF MALIGNANT TRANSFORMATION OF THE ORAL MUCOSA - Wiśniewski, Konrad Oskar; Nowak, Magdalena Natalia; Kuśmierowska, Natalia Sara; Polak, Milena B.; Karolak, Dominika; Słomkowski, Grzegorz; Kuś, Monika; Białowąs, Tymoteusz; Cholewiński, Kacper; Valipur Kolti, Daria (International Journal of Innovative Technologies in Social Science, 2026)
Objective: Swedish snus is a widely used form of smokeless tobacco, often considered a less harmful alternative to cigarette smoking. The aim of this review is to evaluate the impact of long-term snus use on oral mucosal changes and to assess the risk of malignant transformation associated with these lesions. Methods: A narrative review of the literature was conducted, focusing on epidemiology, chemical composition, biological effects, and clinical manifestations of long-term snus use. Studies describing oral mucosal lesions, histopathological features, and cancer risk were analyzed. Results: Long-term use of Swedish snus leads to characteristic oral mucosal changes, most commonly presenting as well-demarcated whitish or yellowish hyperkeratotic lesions at the site of tobacco placement. Histopathological findings include epithelial thickening, hyperkeratosis, and minimal or absent dysplasia. These lesions are typically asymptomatic and often reversible after cessation of snus use. Although snus contains carcinogenic compounds such as tobacco-specific nitrosamines, epidemiological studies indicate a relatively low risk of malignant transformation compared to other forms of smokeless tobacco. No significant increase in oral cancer incidence has been demonstrated among exclusive snus users, although rare cases of malignant transformation have been reported. Conclusions: Swedish snus is not a harmless product and is associated with distinct oral mucosal changes. Despite the relatively low risk of malignant transformation, these lesions require clinical monitoring. Early detection, cessation of use, and appropriate management significantly reduce potential complications. Preventive strategies, including patient education and regular dental examinations, remain essential.